Reliability of blood tests taken from the peripheral intravenous catheter. Issue 28 (15th July 2022) - Ben Shabat, Idan; Ben Shabat, Michal Hoffman; Ben Abraham, Shai; Sagy, Iftach; Tsaban, Gal; Cohen-Lahav, Merav; Goldinger, Gil; Peled, Michal; Bartal, Carmi
Abstract : We aimed to compare the reliability of laboratory blood tests using 2 sampling methods, via a peripheral venous catheter (PVC) vs direct venipuncture stab (DVS), we evaluated the effect of time elapsed since PVC insertion, PVC diameter, and administration of saline and/or antibiotic infusion through PVC on the blood test results. A prospective comparative study was conducted between May 2018 and July 2019. Patients aged ≥ 18 years and admitted to our department with a 20G/22G PVC inserted within the last 24 hours were enrolled. Blood samples were collected from each participant in the morning, and a second sample was drawn using PVC. Dependent variables included the percentage of hemolysis, failure rate, complete blood count, biochemical testing parameters, and coagulation functions. A total of 211 patients participated in the study. In total, 237 blood tests were conducted, of which 167 were performed on day 1 and the remaining on day 2, with a second blood sample collected from 26 patients on day 2. Twenty-one participants received 22G PVC, and 23 participants received active infusion. No significant differences were found in failure rates when each subgroup was compared with the primary day 1 group. The intraclass correlation coefficient indicated significant correlations among all the indices in all groups. Both blood sampling methods (PVC and direct venipuncture) can be used interchangeably for routine laboratory tests on days 1 and 2 after PVC insertion using 20G/22G PVC or infused PVC.